RESTRICTIONS OF THE RIGHTS OF FREEDOM OF RELIGIONS: COMPARISON OF LAW BETWEEN INDONESIA AND GERMANY - Saraswati, A. A. A. Nanda; Wicaksono, Setiawan; Ganindha, Ranitya; Hidayat, M. Choirul (UI Scholars Hub, 2018)
The rights of freedom of religion and beliefs are constitutionally guaranteed, both in Indonesia and Germany. However, the right of freedom of religion is not unlimited. This paper aims to identify and analyze (1) Why there is the right of freedom of religion is restricted, (2) What product of the law is that regulates restriction on the right of freedom of religion in Indonesia and Germany, and (3) What purpose do Indonesia and Germany have in restricting the right of freedom of religion? This paper uses a normative research method that references legislation and takes a historical and comparative approach. The restriction of freedom of religion exists to protect the fundamental right or freedoms for every individual to avoid chaos. The restrictions on freedom of religion in the Indonesian Constitution are stated in Article 28 of the 1945 Constitution, Article 73 of Law No. 39 Year 1999, Article 18 of Law No. 12 Year 2005, and in PNPS No. 1 Year 1965. While Germany does not set explicit restrictions, the environment comes from the level of the Act: namely, Article 166–167 of the Criminal Code. In Indonesia, public order is defined as conformity of justice in consideration of morality, religious values, and security in a democratic society. Meanwhile, Germany defines public order as the protection of society based on the principles of balance and tolerance, in that individual freedoms must be balanced with other people’s fundamental rights, although this also means that a person’s idea of divinity must be excluded.